Transcriptomic Responses to Water Deficit and Nematode Infection in Mycorrhizal Tomato Roots - Balestrini, Raffaella; Rosso, Laura C.; Veronico, Pasqua; Melillo, Maria Teresa; De Luca, Francesca; Fanelli, Elena; Colagiero, Mariantonietta; di Fossalunga, Alessandra Salvioli; Ciancio, Aurelio; Pentimone, Isabella (Frontiers in Microbiology, 2019)
Climate changes include the intensification of drought in many parts of the world, increasing its frequency, severity and duration. However, under natural conditions, environmental stresses do not occur alone, and, in addition, more stressed plants may become more susceptible to attacks by pests and pathogens. Studies on the impact of the arbuscular mycorrhizal (AM) symbiosis on tomato response to water deficit showed that several drought-responsive genes are differentially regulated in AM-colonized tomato plants (roots and leaves) during water deficit. To date, global changes in mycorrhizal tomato root transcripts under water stress conditions have not been yet investigated. Here, changes in root transcriptome in the presence of an AM fungus, with or without water stress (WS) application, have been evaluated in a commercial tomato cultivar already investigated for the water stress response during AM symbiosis. Since root-knot nematodes (RKNs, Meloidogyne incognita) are obligate endoparasites and cause severe yield losses in tomato, the impact of the AM fungal colonization on RKN infection at 7 days post-inoculation was also evaluated. Results offer new information about the response to AM symbiosis, highlighting a functional redundancy for several tomato gene families, as well as on the tomato and fungal genes involved in WS response during symbiosis, underlying the role of the AM fungus. Changes in the expression of tomato genes related to nematode infection during AM symbiosis highlight a role of AM colonization in triggering defense responses against RKN in tomato. Overall, new datasets on the tomato response to an abiotic and biotic stress during AM symbiosis have been obtained, providing useful data for further researches.